Digital media ethics - Ess, Charles 1951- (Digital media and society series, 2020)
"The third edition of this accessible and interdisciplinary textbook has been thoroughly updated to incorporate the latest research and developments, including the rise of Big Data, AI, and the Internet of Things. Digital Media Ethics will continue to be the go-to textbook for anyone getting to grips with this important topic"--Provided by publisher.